The role of financial editing to ensure accuracy and compliance in corporate financial reporting: A case-based study on service-based organisation - Laamari, Imane Ahmed; Bouras, Ahmed; Brika, Said Khalfa (Edelweiss Applied Science and Technology, 2025)
Financial reporting lies at the core of organizational transparency and accountability, particularly among service-based organizations faced with complex financial operations. This paper highlights the extent to which financial editing contributes to accuracy and compliance in systematically reviewing Corporate Financial Reporting. A qualitative case study method was employed in conducting this research, and findings were identified in relation to selected companies operating within the healthcare, technology, and educational sectors in Saudi Arabia. The main findings from this study have shown that financial editing reduces errors and improves compliance, which also bolsters stakeholders' trust. Key findings relate to a 35% and 40% reduction in error and processing time, respectively, with the use of AI-driven tool interventions, while the imperatives for human expertise remain open questions. Resistance to adoption and training needs point toward a strong requirement for managing change. It therefore underscores financial editing as a strategic facilitator in organizational success while at the same time providing useful insights that may be utilized in the pursuit of transparency, accountability, and eventual growth in effective decision-making in fiduciary and complex financial environments. The accompanying implications for future research on its long-term effects include its expansion to integrate with sustainability reporting and blockchain applications.